Validation of a [Al18F]PSMA-11 preparation for clinical applications. (December 2017) - Al-Momani, Ehab; Israel, Ina; Samnick, Samuel
Abstract: Imaging prostate-specific membrane antigen (PSMA) using positron emission tomography (PET) has been presented so far as the most sensitive and specific with regard to prostate cancer detection, in particular in high-risk prostate cancer patients. Currently, it mainly features Gallium-68 ( 68 Ga) labeled PSMA ligands, notably [ 68 Ga]Glu-urea-Lys(Ahx)-HBED-CC ([ 68 Ga]-PSMA-11) and [ 68 Ga]DOTAGA-FFK (Sub-KuE termed ([ 68 Ga]PSMA-I&T). However, 68 Ga has several shortcomings as radionuclide including a short half-life and non-ideal energies. This has motivated consideration of 18 F-labeled analogues for PET imaging of prostate cancer. Here, we describe a simple synthesis and validation of a fluorine-18 labeled Glu-urea-Lys(Ahx)-HBED-CC ([Al 18 F]PSMA-11) for nuclear medicine applications. An efficient method for preparation of [Al 18 F]PSMA-11 was developed and validated (according to Pharm Eur) for routinely clinical applications. [Al 18 F]PSMA-11 was reproducibly obtained in radiochemical yields of 84 ± 6% (n = 15) and > 98% radiochemical purity using an improved one-step radiofluorination in aqueous solution. The total (production/preparation) time, including purification, pharmacological formulation of the isolated product and the quality control of the injectable solution was less than 60 min. The [Al 18 F]PSMA-11 was stable over 4 h in 1% EtOH/saline selected as injection solution. The solution was sterile, non-pyrogenic and ready for clinical applications after sterile filtration through a 0.22 µm membrane filter under sterile conditions. In addition, [Al 18 F]PSMA-11 exhibited higher uptake and retention in PMSA-expressing LNCap prostate cells as compared to its clinically established 68 Ga-labeled analogues [ 68 Ga]PSMA-11 and [ 68 Ga]PSMA-I&T as well as to [ 68 Ga]NOTA-Bn-PSMA. The simple and fast preparation of [Al 18 F]PSMA-11 combined with its favorable pharmacological properties warrant its translation to a clinical setting. Conclusion: The facile and high-yielding radiosynthesis of [Al 18 F]PSMA-11as well as its promising in vitro and in-vivo characteristics makes it worthy of clinical development for PET imaging of prostate cancer. Highlights: An efficient method for preparation of [Al 18 F]PSMA-11 was developed and validated for nuclear medicine applications. [Al 18 F]PSMA-11 was stable in 1% EtOH/saline as sterile and non-pyrogenic injection solution ready for clinical applications. [Al 18 F]PSMA-11 exhibited higher uptake and retention in PMSA-expressing LNCap prostate cells compared to its 68 Ga analogues.